Challenges in Palliative Care Postgraduate Education in Latin America – Time for Collaboration - Pedro E. Perez-Cruz; Alfredo Rodríguez-Núñez; Mhoira Leng; Flavio Nervi Oddole (Palliative Medicine and Hospice Care, 2016)
On May 24th, 2014, the World Health Assembly (WHA) issued the resolution 67.19: “Strengthening of palliative care (PC) as a component of comprehensive care throughout the life course”,1 which crowned the efforts of hundreds of professionals who have worked to extending the field of PC and making it available to everyone, throughout the continuum of care and across all levels.